1997
DOI: 10.3758/bf03211331
|View full text |Cite
|
Sign up to set email alerts
|

Need probability affects retention: A direct demonstration

Abstract: Recent memory theory has emphasized the concept of need probability--that is, the probability that a given piece of learned information will be tested at some point in the future. It has been proposed that, in real-world situations, need probability declines over time and that the memory-loss rate is calibrated to match the progressive reduction in need probability (J.R. Anderson & Schooler, 1991). The present experiments were designed to examine the influence of the slope of the need-probability curve on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
6
33
0
Order By: Relevance
“…Bahrick (1979) found a similar advantage for recall of Spanish-English word lists. Anderson and Schooler (1991) and Anderson et al (1997) model these and analogous results in terms of need probability, showing that accuracy of recall is strongly predicted by degree of expectation for needing the relevant memory trace at test time, based on the intervals between its prior occurrences.…”
Section: Rational Expectation For Repetitionmentioning
confidence: 69%
“…Bahrick (1979) found a similar advantage for recall of Spanish-English word lists. Anderson and Schooler (1991) and Anderson et al (1997) model these and analogous results in terms of need probability, showing that accuracy of recall is strongly predicted by degree of expectation for needing the relevant memory trace at test time, based on the intervals between its prior occurrences.…”
Section: Rational Expectation For Repetitionmentioning
confidence: 69%
“…The general form of MD is not affected by altering time spent encoding (e.g., Wixted & Ebbesen, 1991), time between encoding and testing (Klatzky, 1980), or motivations to remember (R. B. Anderson, Tweney, Rivardo, & Duncan, 1997). GRMA is likewise considered to be an inherent property of goals and motives.…”
Section: From Individuals To Large Populationsmentioning
confidence: 99%
“…For example, R. B. Anderson, Tweney, Rivardo, and Duncan (1997) showed that the rate of decrement in recall of digits was a function of the probability that recall would be required at a given retention interval.…”
Section: Consequences Of Rememberingmentioning
confidence: 99%